PEMELIHARAAN IKAN SELAIS (Ompok sp) DENGAN RESIRKULASI, SISTEM AQUAPONIK - Putra, Iskandar; Pamukas, Niken Ayu (Jurnal Perikanan dan Kelautan, 2011)
Aquaponics, the combined culture of fish and plants in recirculatingsystems,has become increasingly popular. Ammonia that excreted from fishmetabolic activity is a serious problem in intensive aquaculture productionsystems because it would build-up to toxic level in fish tanks. Therefore,recirculating system with filtration process becomes an important component tomaintain water quality in order to be an appropriate condition for fish production.The objective of this experiment was to measure growth and viability fishes withfour media screens Chinese Cabbages with density conduct fishes out selais(Ompok sp) that different. The result of the experiments showed fish performanceof that system such as survival rate, food conversion ratio, and biomass growthrate, were higher than the others, i.e., 100 %, 1.1, and 0,953 kgs, respectively.However, fish specific growth rate of the treatment (1.65 %) have significantdifference (P < 0.05) compared to other treatmen.